2013
DOI: 10.1002/tect.20099
|View full text |Cite
|
Sign up to set email alerts
|

Linking south China to northern Australia and India on the margin of Gondwana: Constraints from detrital zircon U-Pb and Hf isotopes in Cambrian strata

Abstract: Cambrian sedimentary rocks in the southern part of the South China Craton were derived from a source that lay to the south or southeast, beyond the current limits of the craton and which is no longer preserved nearby. U‐Pb ages and Hf isotope data on detrital zircons from the Cambrian sequence define two distinctive age peaks at 1120 Ma and 960 Ma, with εHf(t) values for each group identical to the coeval detrital zircons from Western Australia and the Tethyan Himalaya zone, respectively. The circa 1120 Ma det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
103
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 101 publications
(189 reference statements)
10
103
0
Order By: Relevance
“…Previous studies on lower Paleozoic detrital sedimenatry rocks in the South China Block have also found abundant detrital zircons with Pan-African age and concluded that the South China Block should be linked with and received detritus from North India and Western Australia during the assembly of East Gondwana. Our new data is consistent with and provided more evidence for this conclusion Xu et al, 2013;Zhou et al, 2015).…”
Section: Western Yangtze Marginsupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies on lower Paleozoic detrital sedimenatry rocks in the South China Block have also found abundant detrital zircons with Pan-African age and concluded that the South China Block should be linked with and received detritus from North India and Western Australia during the assembly of East Gondwana. Our new data is consistent with and provided more evidence for this conclusion Xu et al, 2013;Zhou et al, 2015).…”
Section: Western Yangtze Marginsupporting
confidence: 90%
“…Previous detrital zircon data have also shown that Neoproterozoic zircons have both positive and negative εHf(t) values (e.g. Dong et al, 2011;Duan et al, 2011;Wang et al, 2012;Xu et al, 2013;Q.F. Wang et al, 2014;Zhou et al, 2015).…”
Section: Western Yangtze Marginmentioning
confidence: 97%
See 1 more Smart Citation
“…Wang et al, 2007;Li et al, 2010;Li et al, 2013). At the time of orogenesis, South China lie along the northern margin of Gondwana within an overall accretionary orogen that faced the proto-Tethys ocean (Cawood et al, 2007;Wang et al, 2010;Xu et al, 2012;Cawood et al, 2013;Wang et al, 2013;Xu et al, 2013). The Kwangsian orogeny is the local name given to a widespread orogenic pulse that extended along the North Gondwana margin from Turkey to Southeast Asia (Cawood et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Torsvik and Cocks (2009) and Cawood et al (2013), however, plotted the Indochina Block as a discrete block in the paleo-Pacific, far away from the north margin of East Gondwana. In practice, the block was generally omitted in many paleogeographic reconstructions of the Gondwanaland (Li et al, 1995;Cawood and Buchan, 2007;Zhu et al, 2011;Xu et al, 2013). The uncertain paleogeography of the Indochina Block in Gondwana is due to the paucity of good quality of Paleozoic paleomagnetic and reliable geochronological and isotopic data, which has strictly hindered understanding of the position of the block.…”
Section: Introductionmentioning
confidence: 99%